2023
DOI: 10.3390/medicina59071319
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Laser Photocoagulation in Treating Diabetic Macular Edema in the Era of Intravitreal Drug Administration: A Descriptive Review

Abstract: Background and Objectives: This study aimed to elucidate the role of laser photocoagulation therapy in the treatment of diabetic macular edema (DME) as an alternative to, or in conjunction with, the first-line treatment, anti-vascular endothelial growth factor (VEGF). Materials and Methods: A comprehensive literature search to identify studies that evaluated the efficacy of laser photocoagulation therapy in the management of DME was performed. The relevant findings of the efficacy of focal/grid laser therapy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…This study focused on the focal laser combination and anti-VEGF therapies. However, alternative treatment options for anti-VEGF-resistant DME do exist, such as steroid injection 14 , 15 , vitrectomy 16 , 17 , and grid laser therapy 18 20 . Further research should consider other options for treating anti-VEGF-resistant DME to provide a more balanced and informative perspective on DME management.…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on the focal laser combination and anti-VEGF therapies. However, alternative treatment options for anti-VEGF-resistant DME do exist, such as steroid injection 14 , 15 , vitrectomy 16 , 17 , and grid laser therapy 18 20 . Further research should consider other options for treating anti-VEGF-resistant DME to provide a more balanced and informative perspective on DME management.…”
Section: Discussionmentioning
confidence: 99%
“…Laser photocoagulation still plays an important role in the treatment of DR as an adjuvant treatment [ 35 ]. If the anti-VEGF treatment and laser are combined, the number of injections could be reduced [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
“…3,4 LP is considered the gold standard for DME and the only treatment that has been shown to be effective in eliminating retinal neovascularization. 5 However, in some patients, retinal neovascularization may still progress even after laser treatment, and the overall outcome may fall short of clinical expectations. 5,6 Study has found that vascular endothelial growth factor (VEGF) can stimulate angiogenesis, increase its permeability, and accelerate the progress of DME.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Several studies have suggested the superiority of combining laser treatment with anti-VEGF therapy in patients with DME. 5,11 However, most studies only compared the combined therapy with LP alone or ranibizumab alone, and few studies compared all three simultaneously. In recent years, our hospital has adopted the combination of ranibizumab and laser therapy for treating patients with DME.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation